2016
DOI: 10.1590/s1677-5538.ibju.2014.0531
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose-rate brachytherapy for patients with transurethral resection before implantation in prostate cancer. Long-term results

Abstract: Objectives We analyzed the long-term oncologic outcome for patients with prostate cancer and transurethral resection who were treated using low-dose-rate (LDR) prostate brachytherapy.Methods and Materials From January 2001 to December 2005, 57 consecutive patients were treated with clinically localized prostate cancer. No patients received external beam radiation. All of them underwent LDR prostate brachytherapy. Biochemical failure was defined according to the “Phoenix consensus”. Patients were stratified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…From the study by Prada et al [17] published in 2016, we can also draw results that are like those of our series, even though it is a smaller sample of patients, 57 patients were studied, all with previous TUR, from which results were obtained for Survival free of biochemical recurrence, Overall Survival and Survival free of local recurrence. The sample included patients with low and intermediate risk and 40% received hormone therapy for 3 months.…”
Section: Survival Free Of Biochemical Recurrencesupporting
confidence: 83%
“…From the study by Prada et al [17] published in 2016, we can also draw results that are like those of our series, even though it is a smaller sample of patients, 57 patients were studied, all with previous TUR, from which results were obtained for Survival free of biochemical recurrence, Overall Survival and Survival free of local recurrence. The sample included patients with low and intermediate risk and 40% received hormone therapy for 3 months.…”
Section: Survival Free Of Biochemical Recurrencesupporting
confidence: 83%
“…In the study by Prada et al . [ 6 ], 57 patients with clinically localized prostate cancer that underwent LDR brachytherapy were followed up for a period of 10 years. Follow-up 5-year data revealed biochemical control, tumor-free survival, and OS were 94%, 96%, and 88%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several institutions have reported 5- and 10-year biochemical relapse-free survival ranging from 94-96% [ 2 , 3 , 4 ] to 87-98.5% [ 3 , 5 , 6 , 7 ], respectively. In addition, a number of reviews have demonstrated that LDR brachytherapy is equally effective as EBRT or radical prostatectomy (RP) alone in patients with newly diagnosed low- or intermediate-risk prostate cancer [ 8 , 9 , 10 ]; however, Rodrigues et al .…”
Section: Purposementioning
confidence: 99%
“…However, subsequently, Wallner et al reported only a 6% incontinence rate at 3 years in 19 patients treated with prostate seed implant after previous TURP, and there have been a number of retrospective reports of post-TURP brachytherapy with low urinary toxicity rates [6,8,9,24,25,26]. These are shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%